The problem of style in Ludwig Wittgenstein’s philosophy - Klibavičius, Darius (Literatūra, 2009)
The paper deals with a problem of philosophical style in Ludwig Wittgenstein’s (1889–1951) most significant works Tractatus Logico-Philosophicus, Philosophical Investigations and in a posthumous collection of miscellaneous remarks Culture and Value as well. The author performs a comparative analysis between two different writing strategies of Wittgenstein’s philosophy – the analytical and the literary/cultural one. Since the truth is made rather than found, the author states that the problem of truth is replaced by the problem of style in Wittgenstein’s philosophy. This paper extensively discusses Buffon`s statement that “the style is a picture of human being himself”, and the style of writing reveals the philosopher as a creator of literature. According to Wittgenstein, philosophy is not a theory or a doctrine, but rather an activity and clarification of thoughts, so the main principle of Wittgenstein’s philosophy is “showing” rather than “saying”. With the help of this distinction, he tried to overcome the boundary between sayable and unsayable. The concept of “saying” in Wittgenstein’s works is related to systematic philosophy and the other one – that of “showing” – is related to edifying philosophy and poetic pragmatism because namely poetry goes beyond the limits of language not by saying, but by showing and, this way, discloses the noveltyof one’s text as a piece of literature. Creating works in fine arts (sculpture and architecture) Wittgenstein acknowledged the importance of the inseparable unity between the idea and its expression. This paper also highlights the reasons why Wittgenstein used a fragmentary, sketch writing style. The philosopher proposes intentionally to his readers the examples of thinking; still, instead of trying to tell them what things are indeed, he suggests looking at them from different points of view.